2020
DOI: 10.1103/physreve.101.043112
|View full text |Cite
|
Sign up to set email alerts
|

Sediment motion induced by Faraday waves in a Hele-Shaw cell

Abstract: The interaction between the oscillatory boundary-layer flow induced by Faraday waves and a sedimentary granular layer was studied in a Hele-Shaw cell vertically vibrated. The experimental parameters were the vibration frequency f and acceleration a, and the particle diameter dp. At a critical value for the depth of the supernatant fluid layer, ∆hc, it was observed a transition between a flat motionless granular layer and a second regime in which the granular layer undulates and oscillates periodically. For the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Smits et al [8], in turn, identified that Faraday patterns in a BEC present the same behavior as a discrete space-time crystal [9], providing a new scenario for the research of nonequilibrium phase transitions and spontaneus symmetry breaking [10]. Moreover, these excitations have also been explored in superfluid liquid 4 He, where they are a precursor to the formation of classical (non-quantized) vortices [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation

Faraday Waves in strongly interacting superfluids

Hernández-Rajkov,
Padilla-Castillo,
del Río-Lima
et al. 2021
Preprint
“…Smits et al [8], in turn, identified that Faraday patterns in a BEC present the same behavior as a discrete space-time crystal [9], providing a new scenario for the research of nonequilibrium phase transitions and spontaneus symmetry breaking [10]. Moreover, these excitations have also been explored in superfluid liquid 4 He, where they are a precursor to the formation of classical (non-quantized) vortices [11].…”
Section: Introductionmentioning
confidence: 99%
“…Its study dates back to the 19th century when Michael Faraday first observed them on vertically shaken fluids [2]. Faraday waves are, in fact, a ubiquitous phenomenon in non-linear fluids and have been studied in a large variety of systems such as viscoelastic fluids [3], granular media [4], and even in living soft systems such as earth-worms [5]. Naturally, superfluids are not an exception.…”
Section: Introductionmentioning
confidence: 99%

Faraday Waves in strongly interacting superfluids

Hernández-Rajkov,
Padilla-Castillo,
del Río-Lima
et al. 2021
Preprint